The Next Generation Fornax Survey (NGFS): VII. A MUSE view of the nuclear star clusters in Fornax dwarf galaxies - Johnston, Evelyn J.; Puzia, Thomas H.; D’Ago, Giuseppe; Eigenthaler, Paul; Galaz, Gaspar; Häußler, Boris; Mora, Marcelo D.; Ordenes Briceño, Yasna; Rong, Yu; Spengler, Chelsea; Vogt, Frédéric; Côté, Patrick; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Clues to the formation and evolution of nuclear star clusters (NSCs) lie in their stellar populations. However, these structures are often very faint
Gesehen am 18.08.2020